Effect of Thickness on Structural, Morphological, and Optical Properties for Nanocrystalline Thin Films of Cd1-xSnxS, for Optoelectronic Applications (Baghdad Science Journal, 2024)
Thin films of Sn1-xCdxS nanocrystals (X=0,0.7, and 1) with different thicknesses  200, 300, and 400  nm were prepared on glass bases at 300  C by the participation method and chemical spray pyrolysis method (CSP).  The effect of the concentration of Sn and thickness on the structural and optical properties of the prepared films was studied. The films were characterized to evaluate the structure, transmittance, and optical energy band gap. X-ray diffraction (XRD) studies showed that the films were polycrystalline with hexagonal and orthogonal structures. XRD and atomic force measurement results showed that the grain size increases with its thickness. The optical band gap energies and optical transmission and absorption types of the membranes were determined from the optical transmittance spectra. Optical absorption studies in the wavelength range  200-1100 nm  showed that the energy gap values of the films decrease from  2.48-1.95 eV,  2.41-1.92 eV, and  2.3- 1,89 eV with increasing Sn concentration and with increase the thickness  200, 300, and 400 nm respectively. The best properties of the prepared material were determined for its possible use in the manufacture of solar cells.